Experimental study on the failure of loose accumulation landslides under rainfall conditions - Sun, Qianzheng; Zhao, Longhui; Qin, Yigen; Liu, Bangyu (Frontiers in Earth Science, 2023)
Rainfall plays a pivotal role in triggering the failure of loose accumulation landslides. To understand their stability, it is essential to explore the deformation, failure patterns, fine particle migration, and infiltration behavior of such landslides under rainy conditions. Employing the Yuqiupo landslide as a case study, this research dissects the fundamental attributes of the Yuqiupo landslide through ge-ological examinations. Moreover, the study replicates the failure of the loose accumulation land-slide via artificial rainfall experiments. By employing acquired data on soil volumetric water con-tent and matrix suction from these experiments and observing measurable shifts in the landslide's failure progression and rainfall circumstances, the water-hydraulic conditions of the accumulation landslide are meticulously dissected. The conducted experiments disclose that the failure of the loose accumulation landslide emanates from the combined effects of preferential flow and matrix flow within unsaturated conditions. Rainfall triggers an elevation in soil moisture content and a concurrent decrease in matrix suction, compromising the slope's stability and ultimately causing the landslide. Furthermore, our research includes a quantitative analysis of changes in particle size distribution before and after the landslide's failure.This endeavor underscores the influence of dis-tinct failure modes on the migration of fine particles, with these migration patterns distinctly shaped by prevailing rainfall conditions.